ОСОБЛИВОСТІ ПОБУДОВИ ІМПЕДАНСОМЕТРИЧНИХ КАНАЛІВ ДЛЯ РОБОТИ НА НИЗЬКИХ ТА ІНФРАНИЗЬКИХ ЧАСТОТАХ - Борщов, П.І.; Брагинець , І.О.; Масюренко , Ю.О.; Мельник, В.Г. (Інститут електродинаміки НАН України, Київ, 2024)
The features of the low and infra-low frequency ranges of harmonic measurement signals, as well as the properties of the investigated objects, which must be taken into account during the construction of impedance measuring channels, are determined. To combine the necessary metrological characteristics of such channels (accuracy, speed, immunity), an approach is used, consisting in analog-to-digital conversion of signals received from sensors, and subsequent application of digital methods of their processing. Options for implementing this approach using digital methods for determining the amplitude of sinusoidal signals were considered and analyzed, among which the most promising ones were selected for metrological support of impedance measurements at low and infra-low frequencies. The perspective of using parallel-serial analog-digital conversion of an informative signal with its continuous integration at these frequencies is shown. Conclusions were made and recommendations were given regarding the use of the considered methods taking into account the properties of the measurement objects. References 16.